Association between fluoride intake from drinking water and severity of dental fluorosis in Northern and Western Mexico: systematic review and meta-analysis - José Gamarra; David Álvarez-Ordaz; Nelly Molina-Frechero; Leonor Sánchez-Pérez; Alberto Pierdant-Rodriguez; Mario Alberto Isiordia-Espinoza; León Francisco Espinosa-Cristóbal; Marcelo Gómez Palacio-Gastelum; Rogelio González-González; José Salas-Pacheco; Ronell Bologna-Molina (BMC, 2024)
Abstract Background Dental fluorosis (DF) is caused by excessive exposure to fluoride during odontogenesis and leads to various changes in the development of tooth enamel. Some regions in Mexico are considered endemic fluorosis zones due to the high fluoride content in drinking water. The objective of this study was to perform a systematic review and meta-analysis to identify the association between the concentration of fluoride in drinking water and the severity of dental fluorosis in northern and western Mexico. Methods This protocol was registered in the PROSPERO database (ID: CRD42023401519). The search for information was carried out in the PubMed/Medline, Scopus, SpringerLink, and Google Scholar databases between January 2015 and October 2023. The overall relative risk was calculated using the inverse of variance approach with the random effects method. The RoB 2.0 tool was used to construct risk plots. Results Eleven articles were analyzed qualitatively, and most of the included studies presented at least one level of DF severity; six articles were analyzed quantitatively, dividing them into two regions. In North region it was observed a higher prevalence of severe TF cases, corresponding to ≥ TF 5 category (4.78) [3.55, 6.42]. In the West region, most of the included studies presented a higher prevalence of less severe cases, corresponding to ≤ TF 4, in comparison with the North region (0.01) [0.00, 0.52], interpreted as a protective effect. Conclusion The concentrations of fluorides in drinking water are reportedly high in these regions and are directly related to the severity of dental fluorosis experienced by the inhabitants. In the Northern region exists a major concentration of fluoride in drinking water compared with the Western region as well as a prevalence of higher severity cases of dental fluorosis.